THEORETICAL AND METHODICAL ASPECTS OF ATHLETE TRAINING IN UZBEKISTAN - Jamshid Nuraliyevich Eshpulatov; Kamola Bakhadirovna Khakimjonova (Bright Mind Publishing, 2025)
The theoretical and methodological aspects of athlete training in Uzbekistan are influenced by historical traditions, scientific advancements, and modern sports development strategies. The preparation of athletes requires a comprehensive approach that includes physiological, psychological, and technical aspects. In Uzbekistan, sports training methodologies are constantly evolving, incorporating both national experiences and international best practices. This paper explores the fundamental principles and strategies used in training athletes, considering the specificity of different sports, individual athlete characteristics, and the role of sports science in enhancing performance. Additionally, it discusses the impact of state programs, educational institutions, and coaching methodologies in shaping professional athletes in Uzbekistan. The study also addresses the role of technology and innovative approaches in improving training effectiveness.
Keywords: Athlete training, sports methodology, Uzbekistan, coaching strategies, sports science, physical preparation, psychological preparation, performance improvement, sports development, modern training methods.